Pengaruh Pengeluaran Pemerintah Dan Investasiterhadap Pertumbuhan Ekonomi Dan Kesenjanganpendapatan(Studi Empiris Pada Kabupaten/Kotaprovinsi Jawa Barat, Jawa Tengah, Dan Jawa Timur Tahun 2011-2013) - Puntri, Ado Gagarina (2016)
Good economic development is an achievement to be obtained every region in Indonesia. But with the economic growth, investment allocation uneven, as well as the different levels of government spending will lead to inequality and income disparities between regions. The purpose of this study is to analize the effect of government spending and investment to economic growth and the income gap of Regency/City in West Java, Central Java, and East Java 2011-2013. The sample used in this research are all Regencies /Cities in West Java, Central Java, and East Java in 2011-2013. The sampling method by purposive sampling. The number of samples collected as many as 102 regencies/cities. The data outliers 30 regencies/cities of the sample was 72 regencies/cities. In this study, using path analysis ( path analysis). Before the path analysis has been performed classical assumption test. The results showed that government spending does not significantly influence economic growth, while investment positive and significant imp act on economic growth. Furthermore, the partial government spending and investment no significant effect on the income gap, while economic growth is negative and significant effect on the income gap